Poligami dalam Negara-Negara Islam - Bian Ambarayadi; Andi Molawaliada Patodongi (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Polygamy is a problem faced by contemporary society that is considered discrimination against women. Since the beginning of the 20th century, there has been a phenomenon of family law reform in several countries where the majority of the population is Muslim. These countries have reformed Islamic law in family law, triggered by various factors, including political, socio-cultural, economic, and others. This renewal of Islamic law is a new interpretation, where some countries collaborate between Western legal rules and Islamic law. This research aims to study polygamy regulations in nine countries, namely Indonesia, Malaysia, Pakistan, Egypt, Morocco, Jordan, Syria, Turkey, and Tunisia. The method used in this research is a comparative approach to examine the rules of polygamy in the nine countries that are comparing regulations to see the differences and similarities in the rules of polygamy in each country so it can be described according to the group. The results of the discussion show that polygamy in Ulama's view is permissible, and polygamy in 9 Islamic countries can grouped into two, namely, countries that allow polygamy and countries that prohibit polygamy.